Visual Hegemony in the Representations of the Palestinian Cause: Hamas and the Israeli Prisoners - عفيفة حمزة (International Journal of Social Communication, 2025)
This study aimed to uncover the mechanisms of visual hegemony in representations of the Palestinian cause by analyzing images of the Hamas movement and Palestinian prisoners. It also investigated the impact of these representations on public opinion, with a focus on the ethical and humanitarian dimensions conveyed through the images. The study found that visual elements play a central role in shaping public perception of political issues due to their emotional and cognitive influence on audiences. The findings also revealed that Palestinian armed factions treat Israeli prisoners in accordance with humanitarian standards and international humanitarian law. Resistance media emphasized the respectful and compassionate treatment of Israeli prisoners, which contributes to reinforcing the Palestinian narrative by highlighting the ethical dimension in the treatment of detainees contrasted with the repressive policies practiced by Israel.